Enhanced photocatalytic and antibacterial activities of novel Ag-HA bioceramic nanocatalyst for waste-water treatment - Sherif Elbasuney; Ahmed M. El-Khawaga; Mohamed A. Elsayed; Amir Elsaidy; Miguel A. Correa-Duarte (Scientific Reports, 2023)
Abstract Hydroxyapatite (HA), the most common bioceramic material, offers attractive properties as a catalyst support. Highly crystalline mono-dispersed silver doped hydroxyapatite (Ag-HA) nanorods of 60 nm length was developed via hydrothermal processing. Silver dopant offered enhanced chemisorption for crystal violet (CV) contaminant. Silver was found to intensify negative charge on the catalyst surface; in this regard enhanced chemisorption of positively charged contaminants was accomplished. Silver dopant experienced decrease in the binding energy of valence electron for oxygen, calcium, and phosphorous using X-ray photoelectron spectroscopy XPS/ESCA; this finding could promote electron–hole generation and light absorption. Removal efficiency of Ag-HA nanocomposite for CV reached 88% after the synergistic effect with 1.0 mM H2O2; silver dopant could initiate H2O2 cleavage and intensify the release of active ȮH radicals. Whereas HA suffers from lack of microbial resistance; Ag-HA nanocomposite demonstrated high activity against Gram-positive (S. aureus) bacteria with zone of inhibition (ZOI) mm value of 18.0 mm, and high biofilm inhibition of 91.1%. Ag-HA nanocompsite experienced distinctive characerisitcs for utilization as green bioceramic photocatalyst for wastewater treatment.